ASSESSMENT OF THE UFS-QOL QUESTIONNAIRE BEFORE AND AFTER UTERINE ARTERY EMBOLIZATION FOR UTERINE LEIOMYOMA - A.K. BARATOV; F.R. RAKHIMOV; E.L. KALMYKOV (Avicenna Tajik State Medical University, 2020)
Objective: To assess of the quality of life before and after uterine artery embolization (UAE) for uterine leiomyoma. Methods: A survey of 15 women aged 23 to 47 years was conducted using the UFS-QOL questionnaire. The number of fibroids varied from 1 to 6. Fibroids were mainly localized: submucosal (53.3%), intramural (20%), and subserosal (26.7%). Their volume varied in the range of 25.04-294.09 ml. The dominant syndrome in 7 cases was hemorrhagic, in 7 - compression, and in 1 case - their combination. All women underwent UAE. The survey was conducted four times: before, 3, 6 and 12 months after UAE. Results: According to symptom severity subscale of the UFS-QOL questionnaire (8 questions), there was a significant improvement in symptoms 12 months after UAE in comparison with the baseline: a decrease of mean score from 43.3 to 14.0 (p<0.001). Analysis of the health related quality of life (HRQL) subscale (29 questions) also showed a significant improvement in the quality of life after 12 months compared to the initial level: an increase of mean score from 54.3 to 82.8 (p<0.001). The most significant dynamics (p<0.001) was noted for such domains «Concern», «Activities», «Energy/mood», and «Control» (p<0.001). The mean scores for the above domains increased from the baseline values 53.3±16.0; 56.4±18.4; 42.9±18.0 and 53.7±20.1 to 86.0±11.2; 86.9±11.6; 75.2±10.0 and 81.3±11.2 points after 12 months, respectively. For 2 other subsections of the HRQL «Self-consciousness» and «Sexual function», the mean score changes slightly differed: 67.2±32.2 and 71.7±32.9 (initially) and 85.0±12.3 and 86.7±22.4 (after 12 months) (p<0.05 and p<0.01, respectively). The total HRQL mean score also significantly (p<0.001) increased by month 12 from the baseline of 54.3±14.7 to 82.8±7.4. Conclusion: The UFS-QOL questionnaire is a very informative tool for assessing both the severity of the symptoms of uterine fibroids and the quality of life of women who underwent uterine artery embolization. According to the results of the UFS-QOL, a significant dynamics was obtained with respect to both the regression of symptoms of uterine fibroids, and the improvement of all parameters of the quality of life.